The Benefit of Focusing on Air Pollution Instead of Climate Change: How Discussing Power Plant Emissions in the Context of Air Pollution, Rather than Climate Change, Influences Perceived Benefits, Costs, and Political Action for Policies to Limit Emissions. Issue 2 (April 2021) - Hart, P. Sol; Feldman, Lauren
This experiment examines how framing power plant emissions in terms of air pollution or climate change, and in terms of health or environmental impacts, influences perceived benefits and costs of policies to reduce emissions and intentions to take political action that supports such policies. A moderated-mediation model reveals that focusing on air pollution, instead of climate change, has a positive significant indirect influence on intended political action through the serial mediators of perceived benefits and costs. Political ideology moderates the association between perceived benefits and political action. No framing effects are observed in the comparison between health and environmental impacts.